Imparting Self-Care Practices to Therapists: What the Experts Recommend - Thériault, Anne; Gazzola, Nicola; Isenor, Jessica; Pascal, Lisa (Canadian Journal of Counselling and Psychotherapy, 2015)
Therapist self-care has been lauded as a professional and ethical imperative. However, in education and in supervision, self-care themes are relegated to the realm of optional topics. Our objective was to discover what experts believed were the core hardships that should be brought forward in training courses or supervision, and how trainees or supervisees could be coached to develop self-care strategies in response to these challenges. The 26 experts sampled provided detailed responses to structured and open questions. Results indicate that there is agreement regarding the hazards involved in the profession of psychotherapy, that supervisors and educators address hazards through various mechanisms, but that the quest to incorporate self-care into standard academic programs is not unequivocal.